(untitled) (KIUT Publication, 2025)
In this study, histological preparations obtained from various tissues of mice and mouse embryos were examined. The samples were stained using classical dyes such as gloxin and hematoxylin-eosin, and analyzed under light and electron microscopes. Changes such as the condition of the capillary walls, plasma leakage (plasmarhagia), cellular infiltration, and the presence of microthrombi were identified.